Multimorbidity in patients with heart failure from 11 Asian regions: A prospective cohort study using the ASIAN-HF registry - Tromp, Jasper; Tay, Wan Ting; Ouwerkerk, Wouter; Teng, Tiew-Hwa Katherine; Yap, Jonathan; MacDonald, Michael R.; Leineweber, Kirsten; McMurray, John J. V.; Zile, Michael R.; Anand, Inder S.; Lam, Carolyn S. P. (PLoS medicine, 2018)
Comorbidities are common in patients with heart failure (HF) and complicate treatment and outcomes. We identified patterns of multimorbidity in Asian patients with HF and their association with patients' quality of life (QoL) and health outcomes. We used data on 6,480 patients with chronic HF (1,204 with preserved ejection fraction) enrolled between 1 October 2012 and 6 October 2016 in the Asian Sudden Cardiac Death in Heart Failure (ASIAN-HF) registry. The ASIAN-HF registry is a prospective cohort study, with patients prospectively enrolled from in- and outpatient clinics from 11 Asian regions (Hong Kong, Taiwan, China, Japan, Korea, India, Malaysia, Thailand, Singapore, Indonesia, and Philippines). Latent class analysis was used to identify patterns of multimorbidity. The primary outcome was defined as a composite of all-cause mortality or HF hospitalization within 1 year. To assess differences in QoL, we used the Kansas City Cardiomyopathy Questionnaire. We identified 5 distinct multimorbidity groups: elderly/atrial fibrillation (AF) (N = 1,048; oldest, more AF), metabolic (N = 1,129; obesity, diabetes, hypertension), young (N = 1,759; youngest, low comorbidity rates, non-ischemic etiology), ischemic (N = 1,261; ischemic etiology), and lean diabetic (N = 1,283; diabetic, hypertensive, low prevalence of obesity, high prevalence of chronic kidney disease). Patients in the lean diabetic group had the worst QoL, more severe signs and symptoms of HF, and the highest rate of the primary combined outcome within 1 year (29% versus 11% in the young group) (p for all <0.001). Adjusting for confounders (demographics, New York Heart Association class, and medication) the lean diabetic (hazard ratio [HR] 1.79, 95% CI 1.46-2.22), elderly/AF (HR 1.57, 95% CI 1.26-1.96), ischemic (HR 1.51, 95% CI 1.22-1.88), and metabolic (HR 1.28, 95% CI 1.02-1.60) groups had higher rates of the primary combined outcome compared to the young group. Potential limitations include site selection and participation bias. Among Asian patients with HF, comorbidities naturally clustered in 5 distinct patterns, each differentially impacting patients' QoL and health outcomes. These data underscore the importance of studying multimorbidity in HF and the need for more comprehensive approaches in phenotyping patients with HF and multimorbidity. ClinicalTrials.gov NCT01633398.